Gradient positive plate of lithium ion battery and dry preparation method of gradient positive plate
By introducing a high active substance proportion and electrolyte distribution with gradient design into the positive electrode sheet of the lithium-ion battery, the problem of difficult to optimize ion and electron transmission when improving the energy density of the positive electrode materials in the prior art is solved, and the improvement of the energy density of the lithium-ion battery and the optimization of the electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411930688.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While the existing lithium-ion battery positive electrode materials improve energy density, it is difficult to meet the transmission needs of ions and electrons at the same time, resulting in the energy density, rate performance and cycle performance of the battery being unable to be optimized at the same time.
A lithium-ion battery gradient positive electrode sheet is designed. By introducing gradient design into the positive electrode active material, the proportion of high active substances is increased, and the ion transmission path is optimized through the gradient distribution of the electrolyte, thereby achieving optimization of ion transmission in high-load thick electrodes.
The overall energy density of lithium-ion batteries has been improved while maintaining good electrochemical performance, simplifying the preparation process and reducing production costs.
Smart Images

Figure CN119890228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid-state batteries, and in particular to a gradient positive electrode sheet for a lithium-ion battery and a dry preparation method thereof. Background Art
[0002] Traditional lithium-ion battery technology is approaching its energy density limit, and the demand for materials with higher energy density is increasing rapidly. All-solid-state batteries are expected to promote the further development of battery technology due to the high energy density of lithium metal anodes and the high safety of solid-state electrolytes.
[0003] All-solid-state lithium-ion batteries are mainly composed of positive and negative electrodes, current collectors and electrolyte membranes. Composite positive electrode materials are key components that determine the electrochemical performance of all-solid-state battery systems. Increasing the surface capacity and active material ratio of positive electrode materials is an effective way to improve the overall energy density of batteries. However, the increase in the active material ratio and surface capacity will increase the transmission resistance of ions and electrons, resulting in the battery's energy density, rate performance and cycle performance not being able to meet the requirements at the same time.
[0004] At present, the research on improving the energy density of lithium-ion battery positive electrodes mainly includes coating, doping, composition regulation and microstructure design of positive electrode active materials. Material design on the microscale can effectively improve the energy density of lithium-ion batteries, but its application in actual production has higher requirements on preparation process and production equipment, which increases production costs and makes it difficult to achieve large-scale production.
[0005] In order to solve the above problems, the present invention designs a high active material ratio gradient positive electrode sheet with simplified preparation process, improves the overall energy density of the battery by high active material ratio of the positive electrode, and improves the ion transmission path in the thick electrode with high active material ratio by gradient design of the electrolyte, realizes the optimization of ion transmission in the high load thick electrode, and makes full use of the positive electrode active material in the charging and discharging process. The positive electrode sheet effectively improves the energy density of the lithium ion battery while maintaining good electrochemical performance, and simplifies the preparation process and reduces production costs. Summary of the invention
[0006] In order to solve the above problems, a lithium-ion battery gradient positive electrode sheet and a dry preparation method thereof are provided. The positive electrode sheet is a thick positive electrode sheet with a high active material ratio, and is a positive electrode sheet with a gradient distribution of positive electrode active materials and solid electrolytes. It can simultaneously meet high ion transmission and electron transmission under high active material ratio and thick electrode. The positive electrode sheet has high energy density, good cycle stability, low manufacturing cost and simple preparation process, and can achieve an increase in the overall energy density of lithium-ion batteries.
[0007] The present invention is achieved through the following technical solutions:
[0008] A gradient positive electrode sheet for a lithium-ion battery comprises a first positive electrode layer close to a current collector side and a second positive electrode layer away from the current collector side, wherein the first positive electrode layer and the second positive electrode layer are respectively composed of positive electrode active materials, electrolyte materials, conductive agents and adhesives mixed in different proportions, wherein the mass of the positive electrode active material is 80-93 parts, the mass of the electrolyte is 5-17 parts, the mass of the conductive agent is 0-5 parts, and the mass of the adhesive is 0-3 parts.
[0009] During the charging and discharging process of the thick electrode sheet, the transmission path of ions and electrons is long and tortuous. The inventors found that the average proportion of positive electrode active materials reached 85% or more, and the mass difference between the positive electrode active materials of the first positive electrode layer and the positive electrode active materials of the second positive electrode layer was in the gradient range of 3-6. The gradient difference of the electrolyte material can simultaneously optimize the conduction of ions and electrons, thereby improving the overall energy density of the battery.
[0010] The mass of the positive electrode active material in the first positive electrode layer is greater than that in the second positive electrode layer, and the electrolyte concentration in the first positive electrode layer is less than that in the second positive electrode layer.
[0011] The mass ratio of the positive electrode active material, the electrolyte material, the conductive agent and the adhesive in the first positive electrode layer can be 88:10:1:1 or 93:5:1:1, and the mass ratio of the positive electrode active material, the electrolyte material, the conductive agent and the adhesive in the second positive electrode layer can be 82:16:1:1 or 90:8:1:1.
[0012] Positive electrode materials include: layered LiCoO2, ternary layered oxide LiNi x Co y Mn 1-x-y O2(NCM) and LiNi x Co y Al 1-x-y O2(NCA), olivine-type LiFePO4 and spinel-type LiMn2O4, LiMO2(M=Mn,Ni), high-pressure LiNi 0.5 Mn 1.5 O4, high capacity xLi2MnO3·(1-x)LiMO2 or Li 1+x M 1-x O2 (M = Ni, Co, Mn) lithium-rich layered positive electrode, transition metal oxide material, one or more thereof.
[0013] The electrolyte material includes at least one of a sulfide solid electrolyte, a halide solid electrolyte and an oxide solid electrolyte.
[0014] The sulfide solid electrolyte includes one or more of binary sulfides, argyrodite-type Li2S-P2S5-X or ternary sulfides and their derivatives, wherein X=Cl, Br, I.
[0015] The conductive agent material includes: one or more of conductive carbon black (SP), graphite, carbon fiber (VGCF), carbon nanotubes (CNTs) and graphene (GN).
[0016] The binder materials selected in the present invention include: polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylamide (PAM), SA and polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), sodium alginate (Alg), β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), CMC / SBR composite binder, SA / CMC composite binder, one or more thereof;
[0017] More preferably, the binder includes one or more of polyacrylic acid, polyacrylamide, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyvinyl alcohol and / or derivatives or copolymers thereof.
[0018] A method for preparing a gradient positive electrode sheet of a lithium-ion battery with a high active material ratio, comprising the following steps: S1: mixing a positive electrode active material with an electrolyte material, a conductive agent and a binder in different proportions to obtain two mixed positive electrode materials; S2: taking two groups of mixed positive electrode materials obtained in S1, adding binders respectively, and mixing again to obtain two groups of mixed materials; S3: pre-insulating the two groups of mixed materials obtained in S2; S4: fiberizing the pre-insulating mixed materials in S3 to obtain two groups of fiberized mixed positive electrode materials; S5: hot rolling the two fiberized mixed positive electrode materials with different active material ratios in S4 respectively to obtain two groups of composite positive electrode sheets with different active material ratios; S6: superimposing the two groups of composite positive electrode sheets with different active material ratios obtained in S5, hot rolling them, and trimming them to obtain a positive electrode sheet with a gradient distribution of active material ratios.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0020] 1) The gradient positive electrode sheet provided by the present invention has a higher active material ratio, and by adjusting the solid electrolyte ratio, the requirements of lithium ion conductivity at different depths of high-load thick electrode sheets are met, so that the thick electrode positive electrode material is fully utilized, and the energy density of the solid-state battery is improved, which has broad application prospects.
[0021] 2) The gradient positive electrode sheet provided by the present invention has high energy density, good cycle performance, low manufacturing cost and simple preparation process. The gradient positive electrode sheet provided by the present invention has important practical value in the field of solid-state batteries.
[0022] 3) The preparation method of the gradient positive electrode sheet provided by the present invention comprises mixing two groups of positive electrode active materials with electrolytes in different proportions, adding a binder, performing a fiberization treatment after pre-insulation treatment, obtaining a single-layer electrode sheet by multi-stage hot rolling, and finally combining and rolling the two groups of electrode sheets with different active material proportions to obtain a gradient-distributed positive electrode sheet. The present invention can solve the problem of ion transmission obstruction caused by increasing the proportion of positive electrode active materials and surface capacity in order to increase battery energy density. The assembled all-solid-state soft-pack battery has high energy density, good rate performance and cycle performance, and good safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0024] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet of the present invention.
[0025] Figure 2 Process flow chart of dry gradient positive electrode sheet.
[0026] Figure 3 Comparative Examples 1 and 2 capacity utilization curves.
[0027] Figure 4 Capacity utilization curves of Example 1 and Comparative Example 4.
[0028] Figure 5 Capacity utilization curves of Example 2 and Comparative Examples 3 and 5. DETAILED DESCRIPTION
[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing a high energy density composite positive electrode sheet, comprising the following steps:
[0032] A dry composite positive electrode sheet with a gradient distribution of active material ratio, comprising Li(Ni0.89Co0.1Mn 0.01 )O2 ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder. The mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder on the side close to the current collector is 88:10:1:1, and the corresponding ratio on the side close to the electrolyte is 82:16:1:1.
[0033] Step 1: The lithium nickel cobalt manganese oxide positive electrode active material is mixed with the Li6PS5Cl electrolyte material, the SP conductive agent and the PTFE binder in a mass ratio of 88:10:1:1 and 82:16:1:1, respectively, at a rotation speed of 1000 rpm and a mixing time of 15 minutes to obtain two groups of mixed positive electrode materials.
[0034] Step 2: Place the two mixed groups of positive electrode materials in a 100° C. constant temperature drying oven respectively and keep them warm for 2 hours to obtain two groups of heat-insulated positive electrode materials.
[0035] Step 3: The two groups of positive electrode materials after the heat preservation treatment are respectively placed in a high-speed shear mixer for fiberization at a rotation speed of 5000 rpm and a fiberization time of 30 min to obtain two groups of fiberized positive electrode materials.
[0036] Step 4: The two groups of positive electrode materials after the fiberization treatment obtained in step 3 are subjected to multiple horizontal and vertical hot rolling, with the roller temperature being 100°C and the pressure being 1.5t to 3t, to obtain two groups of single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets with different material ratios, and regular single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets are obtained through edge trimming.
[0037] Step 5: The two groups of single-layer positive electrode sheets with different material ratios and the metal aluminum foil are compositely rolled in a double-roll press with a double-roll temperature of 100°C and a pressure of 5t to obtain a dry-process positive electrode sheet with a gradient distribution of nickel-cobalt-manganese active positive electrode materials.
[0038] Example 2
[0039] Different from Example 1, the material ratio of the two groups of positive electrode materials in this embodiment is Li(Ni0.89Co0.1Mn 0.01 )O2 ternary positive electrode material and Li6PS5Cl electrolyte material, VGCF conductive agent and PAA binder are prepared in a mass ratio of 90:8:1:1 and 93:5:1:1. The specific steps are as follows:
[0040] A dry composite positive electrode sheet with a gradient distribution of active material proportions is composed of a nickel-cobalt-lithium manganese oxide ternary positive electrode material, a Li6PS5Cl inorganic solid electrolyte material, a VGCF conductive agent and a PAA binder. The mass ratio of the lithium manganese oxide ternary positive electrode material, the Li6PS5Cl inorganic solid electrolyte material, the VGCF conductive agent and the PAA binder on the side close to the current collector is 93:5:1:1, and the corresponding ratio on the side close to the electrolyte is 90:8:1:1.
[0041] Step 1: The lithium nickel cobalt manganese oxide positive electrode active material is mixed with the Li6PS5Cl electrolyte material, the VGCF conductive agent and the PAA binder in a mass ratio of 90:8:1:1 and 93:5:1:1, respectively, at a rotation speed of 500 rpm and a mixing time of 20 min to obtain two groups of mixed positive electrode materials.
[0042] Step 2: Place the two mixed groups of positive electrode materials in a constant temperature drying oven at 80° C. respectively, and keep them warm for 2 hours to obtain two groups of heat-insulated positive electrode materials.
[0043] Step 3: The two groups of positive electrode materials after the heat preservation treatment are respectively placed in a high-speed shear mixer for fiberization at a rotation speed of 20,000 rpm and a fiberization time of 20 minutes to obtain two groups of fiberized positive electrode materials.
[0044] Step 4: The two groups of positive electrode materials after the fiberization treatment obtained in step 3 are subjected to multiple horizontal and vertical hot rolling, with the roller temperature being 100°C and the pressure being 1.5t to 5t, to obtain two groups of single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets with different material ratios, and regular single-layer composite lithium manganese oxide dry-process positive electrode sheets are obtained through edge trimming.
[0045] Step 5: The two groups of single-layer positive electrode sheets with different material ratios and the metal aluminum foil are compositely rolled in a double-roll press with a double-roll temperature of 100°C and a pressure of 8t to obtain a dry-process positive electrode sheet with a gradient distribution of lithium manganese oxide active positive electrode material.
[0046] Example 3
[0047] Different from Example 1, the material ratio of the two groups of positive electrode materials in this embodiment is LiFePO4 positive electrode active material and Li6PS5Cl electrolyte material, SP conductive agent and PAA binder in a mass ratio of 82:16:1:1 and 88:10:1:1. The specific steps are as follows:
[0048] A dry composite positive electrode sheet with a gradient distribution of active material proportions is composed of a lithium iron phosphate positive electrode material, a Li6PS5Cl inorganic solid electrolyte material, an SP conductive agent and a PAA binder. The mass ratio of the lithium iron phosphate positive electrode material, the Li6PS5Cl inorganic solid electrolyte material, the SP conductive agent and the PAA binder on the side close to the current collector is 88:16:1:1, and the corresponding ratio on the side close to the electrolyte is 82:10:1:1.
[0049] Step 1: The lithium iron phosphate positive electrode active material is mixed with the Li6PS5Cl electrolyte material, the SP conductive agent and the PAA binder in a mass ratio of 82:16:1:1 and 88:10:1:1, respectively, at a rotation speed of 800 rpm and a mixing time of 15 min to obtain two groups of mixed positive electrode materials.
[0050] Step 2: Place the two mixed groups of positive electrode materials in a constant temperature drying oven at 80° C. respectively, and keep them warm for 2 hours to obtain two groups of heat-insulated positive electrode materials.
[0051] Step 3: The two groups of positive electrode materials after the heat preservation treatment are respectively placed in a high-speed shear mixer for fiberization at a rotation speed of 10,000 rpm and a fiberization time of 25 minutes to obtain two groups of fiberized positive electrode materials.
[0052] Step 4: The two groups of positive electrode materials after the fiberization treatment obtained in step 3 are subjected to multiple horizontal and vertical hot rolling, with the roller temperature being 100°C and the pressure being 1.5t to 3t, to obtain two groups of single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets with different material ratios, and regular single-layer composite lithium iron phosphate dry-process positive electrode sheets are obtained through edge trimming.
[0053] Step 5: The two groups of single-layer positive electrode sheets with different material ratios and the metal aluminum foil are compositely rolled in a double-roll press with a double-roll temperature of 100°C and a pressure of 8t to obtain a dry-process positive electrode sheet with a gradient distribution of lithium iron phosphate active positive electrode material.
[0054] Example 4
[0055] Different from Example 1, the material ratio of the two groups of positive electrode materials in this embodiment is LiCoO2 positive electrode active material and Li6PS5Cl electrolyte material, CNT conductive agent and PAA binder in a mass ratio of 82:16:1:1 and 88:10:1:1. The specific steps are as follows:
[0056] A dry composite positive electrode sheet with a gradient distribution of active material proportions is composed of a lithium cobalt oxide positive electrode material, a Li6PS5Cl inorganic solid electrolyte material, a CNT conductive agent and a PAA binder. The mass ratio of the lithium cobalt oxide positive electrode material, the Li6PS5Cl inorganic solid electrolyte material, the CNT conductive agent and the PAA binder on the side close to the current collector is 88:16:1:1, and the corresponding ratio on the side close to the electrolyte is 82:10:1:1.
[0057] Step 1: The lithium cobalt oxide positive electrode active material is mixed with the Li6PS5Cl electrolyte material, the CNT conductive agent and the PAA binder in a mass ratio of 82:16:1:1 and 88:10:1:1, respectively, at a rotation speed of 1000 rpm and a mixing time of 20 min to obtain two groups of mixed positive electrode materials.
[0058] Step 2: Place the two mixed groups of positive electrode materials in a constant temperature drying oven at 80° C. respectively, and keep them warm for 2 hours to obtain two groups of heat-insulated positive electrode materials.
[0059] Step 3: The two groups of positive electrode materials after the heat preservation treatment are respectively placed in a high-speed shear mixer for fiberization at a rotation speed of 15000 rpm and a fiberization time of 25 min to obtain two groups of fiberized positive electrode materials.
[0060] Step 4: The two groups of positive electrode materials after the fiberization treatment obtained in step 3 are subjected to multiple horizontal and vertical hot rolling, with the roller temperature being 100°C and the pressure being 1.5t to 3t, to obtain two groups of single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets with different material ratios, and regular single-layer composite lithium cobalt oxide dry-process positive electrode sheets are obtained through edge trimming.
[0061] Step 5: The two groups of single-layer positive electrode sheets with different material ratios and the metal aluminum foil are compositely rolled in a double-roll press with a double-roll temperature of 100°C and a pressure of 5t to obtain a dry-process positive electrode sheet with a gradient distribution of lithium cobalt oxide active positive electrode material.
[0062] Comparative Example 1 (no gradient for active material, positive gradient for conductive agent)
[0063] The difference from Example 1 is that the material ratio of the two groups of positive electrode materials is Li(Ni0.89Co0.1Mn 0.01 ) The mass ratios of O2 positive electrode active material, Li6PS5Cl electrolyte material, SP conductive agent and PTFE binder are 85:13:1:1 and 85:14:0:1, and the specific steps are as follows:
[0064] A dry composite positive electrode sheet with a gradient distribution of active material ratio, comprising Li(Ni0.89Co0.1Mn 0.01 )O2 ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder. The mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder on the side close to the current collector is 85:13:1:1, and the corresponding ratio on the side close to the electrolyte is 85:14:0:1.
[0065] Step 1: The lithium nickel cobalt manganese oxide positive electrode active material is mixed with the Li6PS5Cl electrolyte material, the SP conductive agent and the PTFE binder in a mass ratio of 85:13:1:1 and 85:14:0:1, respectively, at a rotation speed of 1500 rpm and a mixing time of 10 min to obtain two groups of mixed positive electrode materials.
[0066] Step 2: Place the two mixed groups of positive electrode materials in a 100° C. constant temperature drying oven respectively and keep them warm for 2 hours to obtain two groups of heat-insulated positive electrode materials.
[0067] Step 3: The two groups of positive electrode materials after the heat preservation treatment are respectively placed in a high-speed shear mixer for fiberization at a rotation speed of 7000 rpm and a fiberization time of 30 min to obtain two groups of fiberized positive electrode materials.
[0068] Step 4: The two groups of positive electrode materials after the fiberization treatment obtained in step 3 are subjected to multiple horizontal and vertical hot rolling, with the roller temperature being 100°C and the pressure being 1.5t to 5t, to obtain two groups of single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets with different material ratios, and regular single-layer composite nickel-cobalt-manganese dry-process positive electrode sheets are obtained through edge trimming.
[0069] Step 5: The two groups of single-layer positive electrode sheets with different material ratios and the metal aluminum foil are compositely rolled in a double-roll press with a double-roll temperature of 100°C and a pressure of 5t to obtain a dry-process positive electrode sheet with a gradient distribution of nickel-cobalt-manganese active positive electrode materials.
[0070] Comparative Example 2
[0071] Different from Example 1, the mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder on the side close to the current collector is 85:14:0:1, and the corresponding ratio on the side close to the electrolyte is 85:13:1:1.
[0072] Comparative Example 3
[0073] Different from Example 2, the mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder on the side close to the current collector is 93:5:1:1, and the corresponding ratio on the side close to the electrolyte is 90:8:1:1.
[0074] Comparative Example 4
[0075] Different from Example 1, the electrode sheet is a single piece, and the positive electrode active material and the like are uniformly distributed with a non-gradient distribution. The mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder is 85:13:1:1.
[0076] Comparative Example 5
[0077] Different from Example 2, the electrode sheet is a single piece, the positive electrode active material and the like are uniformly distributed with a non-gradient distribution, and the mass ratio of the cobalt-manganese ternary positive electrode material, Li6PS5Cl inorganic solid electrolyte material, SP conductive agent and PTFE binder is 91.5:6.5:1:1.
[0078] From the above embodiments and comparative examples and in combination with the attached Figure 3-5From Examples 1-4 and Comparative Examples 1-5, it can be seen that the first cycle discharge capacity of the positive gradient thick electrode with an average active material content of 85% shown in Example 1 is 210.35 mAh·g -1 The first cycle discharge capacity of the thick electrode with positive gradient distribution of conductive agent shown in Comparative Example 1 is 206.60 mAh·g -1 , compared with 207.53 mAh·g shown by the reverse gradient distribution of the conductive agent in Comparative Example 2. -1 There is no obvious difference. Comparative Example 1 combined with Comparative Example 2 shows that the conductive agent is not the main influencing factor, and although the proportion of active materials is 85% on average, the gradient difference of the active material mass is zero, so that its discharge capacity is not very large. The positive active material mass difference is 3-6, and the double-layer composite electrode sheet with a mass average of more than 85% has a higher discharge capacity. The reverse (reverse) gradient and uniform positive active material, that is, the comparative example that is not within the scope of the above embodiment, has a poor final effect.
[0079] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A gradient positive electrode sheet for a lithium-ion battery, characterized in that: The average proportion of active materials in the positive electrode sheet is 85% or more. The electrode sheet includes a first positive electrode layer close to the current collector side and a second positive electrode layer away from the current collector side. The first positive electrode layer and the second positive electrode layer are respectively composed of positive electrode active materials, electrolyte materials, conductive agents and adhesives mixed in different proportions, wherein the mass of the positive electrode active material is 80-93 parts, the mass of the electrolyte is 5-17 parts, the conductive agent is 0-5 parts, and the adhesive is 0-3 parts.
2. The positive electrode sheet according to claim 1, characterized in that: The mass of the positive electrode active material in the first positive electrode layer is greater than that in the second positive electrode layer, and the electrolyte concentration in the first positive electrode layer is less than that in the second positive electrode layer.
3. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the electrolyte material, the conductive agent and the adhesive in the first positive electrode layer can be 88:10:1:1 or 93:5:1:1, and the mass ratio of the positive electrode active material, the electrolyte material, the conductive agent and the adhesive in the second positive electrode layer can be 82:16:1:1 or 90:8:1:
1.
4. The positive electrode sheet according to claim 1, characterized in that: Positive electrode materials include: layered LiCoO2, ternary layered oxide LiNi x Co y Mn 1-x-y O2(NCM) and LiNi x Co y Al 1-x-y O2(NCA), olivine-type LiFePO4 and spinel-type LiMn2O4, LiMO2(M=Mn,Ni), high-pressure LiNi 0.5 Mn 1.5 O4, high capacity xLi2MnO3·(1-x)LiMO2 or Li 1+x M 1-x O2 (M = Ni, Co, Mn) lithium-rich layered positive electrode, transition metal oxide material, one or more thereof.
5. The positive electrode sheet according to claim 1, characterized in that: The electrolyte material includes at least one of a sulfide solid electrolyte, a halide solid electrolyte and an oxide solid electrolyte.
6. The positive electrode sheet according to claim 5, characterized in that: The sulfide solid electrolyte includes one or more of binary sulfides, argyrodite-type Li2S-P2S5-X or ternary sulfides and their derivatives, wherein X=Cl, Br, I.
7. The positive electrode sheet according to claim 1, characterized in that: The conductive agent material includes: one or more of conductive carbon black, graphite, carbon fiber, carbon nanotube and graphene.
8. The method for preparing a positive electrode sheet according to any one of claims 1 to 7, characterized in that: S1: The positive electrode active material is mixed with the electrolyte material, the conductive agent and the binder in different proportions to obtain two mixed positive electrode materials; S2: The two groups of mixed positive electrode materials obtained in S1 are taken, the binders are added respectively, and the mixtures are mixed again to obtain two groups of mixed materials; S3: The two groups of mixed materials obtained in S2 are pre-insulated; S4: The pre-insulated mixed materials in S3 are fiberized to obtain two groups of fiberized mixed positive electrode materials; S5: The fiberized mixed positive electrode materials with different active material proportions in S4 are respectively hot-rolled to obtain two groups of composite positive electrode sheets with different active material proportions; S6: The two groups of composite positive electrode sheets with different active material proportions obtained in S5 are stacked and hot-rolled, and edge trimming is performed to obtain positive electrode sheets with a gradient distribution of active material proportions.
Citation Information
Patent Citations
Electrode pole piece, preparation method thereof and solid-state battery
CN110581253A
All-solid-state battery with low interface impedance and high interface compatibility
CN111092254A
Positive electrode material layer suitable for all-solid-state battery, preparation method of positive electrode material layer, positive plate and all-solid-state battery
CN112133921A
Integrated composite positive pole piece with solid electrolyte layer and preparation method of integrated composite positive pole piece
CN118867139A
Electrode for solid-state battery and solid-state battery
JP2021039849A
Cited By
A full-solid-state battery gradient positive electrode sheet based on an integrated halide functional layer
CN122659013A